1994
DOI: 10.1007/bf00225157
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of early generation selections for yield and related characters in safflower (Carthamus tinctorius L.)

Abstract: The efficiency of early generation selection for yield and related characters in safflower (Carthamus tinctorius L.) was studied in the F2, F3 and F4 generations. Twenty-five F2 progenies derived from various crosses were studied. In the F2 generation, number of capitula per plant (CNSP), number of seeds per capitulum (SPSP), test weight (SWSP), and seed yield (SYSP) were the criteria used for single plant selection. The analysis of variance showed significant differences for all of the characters in the F2, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The large differences in the level of population differentiation among populations across the Middle East may reflect different histories of these populations and the consequent different allocation of genetic variation among and within populations (Lahane et al 1999;Hernandez-Verdugo et al 2001). The exceptionally high within population variation in this germplasm collection is expected to be maintained or even maximized by a combination of genetic, environmental (Patel et al 1994) and management factors (Assefa et al 1999) across its geographical region of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…The large differences in the level of population differentiation among populations across the Middle East may reflect different histories of these populations and the consequent different allocation of genetic variation among and within populations (Lahane et al 1999;Hernandez-Verdugo et al 2001). The exceptionally high within population variation in this germplasm collection is expected to be maintained or even maximized by a combination of genetic, environmental (Patel et al 1994) and management factors (Assefa et al 1999) across its geographical region of adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Traits such as number of primary branches and heads per plant influence seed yield (Ashri et al, 1974 ; Patil et al, 1994 ; Dajue and Mündel, 1996 ). We found significant variation in the above traits and accessions with high number of primary branches and increased number of heads were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Under water stress conditions, this value was a little lower (88.5%) indicating that visual selection of the best single plant is still highly effective under both water stress and non-stress conditions. Patil et al (1994) has also showed that SPS could be an effective breeding strategy for improving SY of safflower in early segregating generations.…”
Section: Discussionmentioning
confidence: 99%
“…In these methods, competition and natural selection effects will be negligible and genetic variation will be conserved during the segregating generations. Patil et al (1994) has shown effectiveness of SPS for seed yield of safflower in F3 and F4 generations. In comparing four selection methods in wheat (Triticum aestivum L.), it was shown that SPS and single seed descent (SSD) were superior to the bulk population (BP) and mechanical mass selection (MMS) in the F3 generation for grain yield (Srivastava et al, 1989).…”
mentioning
confidence: 95%